Salivary cortisol in top-level professional soccer players - Moreira, A.; Arsati, F.; Arsati, Y. B. de O. L.; da Silva, D. A.; de Araújo, V. C. (European Journal of Applied Physiology, 2009)
We have tested the hypothesis that salivary cortisol increases after a competitive training match in top-level male professional soccer players divided in team A (n = 11) versus team B (n = 11). Saliva samples collected before and after the match were analyzed. Salivary cortisol concentrations were measured by enzyme-linked immunosorbent assay. The results from a two-way ANOVA with repeated measures showed no significant changes in salivary cortisol between either teams or time points (P > 0.05). Further investigation regarding competitive matches in a competition environment is warranted. In summary, the influence of intensive competitive training match alone appears to be minimal on salivary cortisol changes in top-level soccer adapted to this type of stress. From a practical application, the variability of the responses among the players leads us to suggest that there is a need to individually analyse the results with team sports.